Machining performance of 22MnB5 Boron steel cutting tool with Al 6061 Aluminium Alloy - Mohd Rashid, Mohd Fairuz (2021)
Machining is a process to manufacture a product by removing portion of material by using cutting tool. In machining aluminium alloy, the usage of high speed steel (HSS) cutting tool have dominant due to versatility and superior hardness. However, HSS cutting tool is very prone to wear in high-speed machining due to the low hot hardness. Such condition affected productivity as worn cutting tool detrimental to the machined surface and the production need to stop to replace the cutting tool. In the recent advancement of machine tool technology, a new type of steel already applied for automotive structure. This steel, named as 22MnB5 Boron Steel, produced by the hot stamping process where the sheet metals were formed and heat treated inside metal stamping dies. 22MnB5 Boron Steel categorized as ultra-high strength steel with 1500 MPa tensile strength and 80 HRC hardness. Such properties resembled almost similar to HSS which make them potential to be applied as cutting tool. The purpose of this study is to investigate the capability of 22MnB5 Boron Steel as a cutting tool in machining aluminium alloy. Initial part of study involved with analysis on the physical and mechanical properties of 22MnB5 in terms of hardness, density, tensile strength, surface appearance and coefficient of friction. The second part covers machining trials of 22MnB5 Boron steel on Al 6061 Aluminum Alloy using various condition and parameters. Lastly the third parts cover assessment of failure modes and wear mechanism of 22MnB5. The results show that combination of high hardness of 70HRC, density of 7.841 g/cm3 and tensile strength of 1500 MPa facilitate strong edge of 22MnB5 to machine Al 6061 smoothly. 22MnB5 capable to machine Al 6061 Aluminum Alloy in wet condition up to 861 s at 200 m/min, 0.1 mm/rev and 0.5 mm cutting speed, feed rate and depth of cut respectively. The wear mechanism showed up as fragmented debris and built up layer dominated the flank and crater surfaces with abrasive and adhesive effects. This study built better understanding of 22MnB5 characterization in operation that involved with friction, tribology and machining. Finding from this study could also benefit the industries in terms of selection of cutting tools that capable to machine product with sustainable manufacturing approach.